Market power in the EU banking sector in a time of unconventional monetary policy - Ortega, Cristina (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: This paper investigates how market power has evolved in the EU banking sector during a period of unconventional monetary policy, particularly under negative interest rates. Methodology: The author estimated an adjusted Lerner index through stochastic frontier analysis applied to an unbalanced panel of 272 EU commercial banks from 2015 to 2019, accounting for contextual factors including monetary policy stance, financial system development and regulatory environment. Results: The findings show that the traditional Lerner index overstated market power in EMU countries due to near-zero interest rates. The adjusted index reveals lower market power in EMU banks and consistently higher levels in non-EMU countries, especially the UK and the Nordic countries. Implications and recommendations: The findings emphasise the need to consider monetary policy and institutional factors in competition analysis. Future research should explore how banks adjust pricing under persistent low-rate environments. Originality/value: This paper offers a refined measure of bank market power that corrects for biases in standard metrics during periods of unconventional monetary policy, enhancing cross-country comparability within the EU.
Argumenta Oeconomica, 2025, Nr 2 (55), s. 181-203
Keywords: market power; stochastic frontier; Lerner index; banking